The Deterrent Effect of Whistleblowing on Insider Trading - Raleigh, Jacob (Journal of Financial and Quantitative Analysis, 2024)
Abstract I study whether the Dodd–Frank whistleblower program reduced informed trading by corporate insiders. To identify the effect, I partition firms based on the extent to which this program affected the likelihood of whistleblowing at each firm. I find a relative reduction in trading profits on purchases made by insiders at more affected firms after the program was initiated. I analyze insider sales in settings where they are more likely to be informed and find a reduction in the number of sales before negatively perceived events. The results suggest that whistleblower protections and rewards can effectively deter insider trading.